Network Pharmacology and Experimental Evidence: PI3K/AKT Signaling Pathway is Involved in the Antidepressive Roles of Chaihu Shugan San - Zhang S; Lu Y; Chen W; Shi W; Zhao Q; Zhao J; Li L (Dove Medical Press, 2021)
Shan Zhang,1 Yujia Lu,1 Wei Chen,2 Wei Shi,1 Qian Zhao,1 Jingjie Zhao,1,3 Li Li1,3 1Department of Traditional Chinese Medicine, Beijing Friendship Hospital, Capital Medical University, Beijing, 100050, People's Republic of China; 2Experimental and Translational Research Center, Beijing Friendship Hospital, Capital Medical University, Beijing, 100050, People's Republic of China; 3Department of Integrated Traditional and Western Medicine, Capital Medical University, Beijing, 100050, People's Republic of ChinaCorrespondence: Jingjie Zhao; Li LiDepartment of Traditional Chinese Medicine, Beijing Friendship Hospital, Capital Medical University, NO. 95 Yong-an Road, Beijing, 100050, People's Republic of ChinaTel/Fax +86 10-63139096Email zhaojj@ccmu.edu.cn; lili@ccmu.edu.cnObjective: Chaihu Shugan San (CSS) is a common antidepressant prescription in traditional Chinese medicines. However, its active ingredients and mechanisms are unknown. The aim of this study was to explore the potential active ingredients and pharmacological mechanisms of CSS for the treatment of major depressive disorder (MDD).Methods: Active compounds in CSS were screened using the Traditional Chinese Medicine Systems Pharmacology database. Compound-related targets were retrieved using the SwissTargetPrediction database. MDD-related targets were determined using DisGeNET, Therapeutic Target Database and DrugBank databases. The common targets of active compounds in CSS and MDD were retained to construct a compound-MDD target network. Then, functional enrichment analysis and protein-protein interaction analysis were performed to identify hub targets and explore the underlying molecular mechanisms. Finally, hub-targeted genes and pathways were validated by Western blotting and immunofluorescence using chronic unpredictable mild stress (CUMS) mice with or without CSS treatment. The affinities between the active compounds in CSS and hub-targeted genes were evaluated by molecular docking.Results: Network pharmacology analysis revealed 24 potential targets for treatment of MDD by CSS. Functional enrichment analysis showed that PI3K/AKT signaling pathway was likely to be evidently affected by CSS in the treatment of MDD. In vivo experiments showed that CSS could improve depressive-like behaviors and promote neurogenesis in CUMS mice. Furthermore, CSS could increase phosphorylated (p) PI3K/PI3K and pAKT/AKT levels and decrease the pGSK3β/GSK3β level in the hippocampus of CUMS mice. The active compounds mainly included quercetin and luteolin, which showed good docking scores targeting the PI3K protein.Conclusion: This network pharmacological and experimental study highlights that the PI3K/AKT pathway is the potential mechanism by which CSS is involved in MDD treatment. Quercetin, luteolin, and kaempferol are probable active compounds in CSS, and these results might provide valuable guidance for further studies of MDD treatment.Keywords: Chaihu Shugan San, major depressive disorder, network pharmacology, PI3K/AKT signaling pathway